Comparison of Mineral Oil, Insecticidal, and Biopesticide Spraying Regimes for Reducing Spread of Three Potato virus Y Strains in Potato Crops - MacKenzie, Tyler D B (Plant disease, 2022)
In-field management of Potato virus Y (PVY) faces challenges caused by the changing availability and environmental acceptability of chemical agents to control aphid vectors of the virus and by proliferation of PVY strains with different symptoms and rates of spread. From 2018 to 2020, foliar spray treatments were compared in field experiments in New Brunswick, Canada, to measure effectiveness at reducing spread of PVYO, PVYN:O, and PVYNTN strains. Mineral oil, insecticide, combined oil and insecticide spray, and a biopesticide (i.e., LifeGard WG) were compared. Insecticide-only and mineral oil-only treatments were not effective, but several combined oil and insecticide treatments and biopesticide treatments significantly reduced PVY spread. The biopesticide was proportionately more effective with recombinant PVYN:O and PVYNTN strains, possibly by exciting the plant's hypersensitive resistance response, caused naturally only in cultivar 'Goldrush' by PVYO. Pesticide residue analysis showed that mineral oil increased the retention of pyrethroid insecticide in the potato foliage longer than with insecticide applied alone, which may explain the beneficial synergistic effect of combined sprays for reducing PVY spread. Tuber yields were generally unchanged in chemical insecticide treatments but were slightly lower in biopesticide treatment. The cost per PVY treatment was competitive across all effective treatments, including biopesticide; however, there was some revenue loss from lower yield with the biopesticide. This biopesticide is certified organic, however, and thus a small premium on the price for organic production could offset this yield deficit